Surgical treatment for old subaxial cervical dislocation with bilateral locked facets in a 3-year-old girl: A case report. Issue 18 (May 2018) - Li, Cheng; Li, Lei; Duan, Jingzhu; Zhang, Lijun; Liu, Zhenjiang
Abstract: Rationale: This study aimed to describe the case of a 3-year-old girl with old bilateral facet dislocation on cervical vertebrae 6 and 7, who had spinal cord transection, received surgical treatment, and achieved a relative satisfactory therapeutic effect. Patient concerns: A 3-year-old girl was urgently transferred to the hospital after a car accident. Diagnoses: she was diagnosed with splenic rupture, intracranial hemorrhage, cervical dislocation, spinal transection, and Monteggia fracture of the left upper limb. Interventions: The girl underwent emergency splenectomy and was transferred to the intensive care unit of the hospital 15 days later. One-stage anterior–posterior approach surgery (anterior discectomy, posterior laminectomy, and pedicle screw fixation) was performed when the patient stabilized after 45-day symptomatic treatment. The operation was uneventful. Outcomes: The reduction of lower cervical dislocation was satisfactory, with sufficient spinal cord decompression. The internal fixation position was good, and the spinal sequence was well restored. The girl was discharged 2 weeks later after the operation and followed up for 2 years. The major nerve function of both upper limbs was recovered, with no obvious retardation of the growth of immature spine. Lessons: A satisfactory therapeutic effect was achieved for a pediatric old subaxial cervical dislocation with bilateral locked facets using anterior discectomy, posterior laminectomy, and pedicle screw fixation. The posterior pedicle screw fixation provided a good three-dimensional stability of the spine, with reduced risk and complications caused by anterior internal fixation. The growth of immature spine was not obviously affected during the 2-year follow-up.